Polychlorinated organic pollutants (PCDD/Fs and DL-PCBs) in loggerhead (Caretta caretta) and green (Chelonia mydas) turtles from Central-Southern Tyrrhenian Sea. (January 2021) - Lambiase, Sara; Serpe, Francesco Paolo; Pilia, Marisa; Fiorito, Filomena; Iaccarino, Doriana; Gallo, Pasquale; Esposito, Mauro
Abstract: This study assesses for the first time the levels of PCDD/Fs and DL-PCBs in sea turtles coming from Tyrrhenian Sea. The concentrations measured in liver of the 24 specimens analysed were 6.90 vs 5.65 pg g −1 wet weight (ww) for PCDD/Fs and 10.95 vs 0.79 ng g −1 ww for DL-PCBs in Caretta caretta and Chelonia mydas, respectively . The DL-PCB levels resulted very higher in Caretta caretta than Chelonia mydas probably due to the different eating habits between the two species investigated. Furthermore, the highest levels of DL-PCBs were determined in livers of the adult Caretta caretta turtles of male sex. Positive correlations were found out between PCB-81 and the body mass (BM) of turtles (r 2 = 0.6561; p = 0.001) and between PCB-81 and the curved carapace length (CCL) (r 2 = 0.6250; p = 0.006) suggesting that the body burden of contaminants is related to the body size. The mean TEQ values, as a matter of risk assessment for turtles, were 3.64 vs 1.62 pg TEQ g −1 ww for PCDD/Fs and 8.72 vs 2.16 pg TEQ g −1 ww for DL-PCBs in Caretta caretta and Chelonia mydas, respectively. The results reported in this study increase the data available about the consequences of the Mediterranean Sea contamination by organochlorine pollutants and highlight an evident PCDD/F and PCB bioaccumulation in sea turtle tissues that threatens the survival of these marine organisms. Highlights: Turtles bioaccumulate levels of PCDD/Fs lower than DL-PCBs. Turtles living in contaminated areas accumulate high levels of PCBs in liver. PCB profiles found in turtles are similar to the patterns of commercial mixtures. Female turtles show lower concentrations of PCBs in their tissues than males.